Impact of Technological Innovation and New Economic Policies on Traditional Industries: A study of Coir Industry in Alappuzha and Kayamkulam, Kerala - Pranav Sujay (Tata Institute of Social Sciences, 2018)
The neo-liberal, new economic policies which got implemented in 1991, can be classified as a class project, representing the demands of the capitalist class. These policies had, thus, serious repercussions on the livelihood of the working class, as they transformed the modes of production by reinforcing the use of technology. State neglect of the rural areas and decreasing rural development expenditure further fuelled the issue. In this context, this study draws focus to the coir industry of Kerala. The research will be primarily an impact assessment of the new economic policies and its repercussions on the working class, with focus within the framework of coir industry of Kerala. This research is primarily a qualitative analysis but uses quantitative data to make and strengthen arguments. The study recognises the continued state intervention by the state through a co-operative framework even after the Indian scenario witnessed a decreased state intervention. The introduction of machines further strengthened the existing division of labour, wherein labourers were allotted different machineries on the basis of their age, gender and skill set possessed. It also deviates from the mainstream approach and argues that the technological change associated with the neo-liberal policies has improved the quality of life of the coir workers of Kerala rather than causing large-scale retrenchment of workers.